Analysis of Problems and Solutions of Slums in Siantar Estate, Huta Melati, Simalungun Regency - Panatar Pakpahan; Abdi Sugiarto (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study aims to examine the Analysis of Problems and Solutions of Slum Areas in Siantar Estate, Huta Melati, Simalungun Regency. This study uses a qualitative research design with a phenomenological approach. In this context, researchers seek to understand how people in slums interpret their living conditions and the challenges they face. The research was conducted in the slums of Siantar Estate and Huta Melati, Simalungun Regency. Data Collection Techniques are collected through several techniques, including: In-Depth Interviews Interviews are conducted with residents and community leaders to dig up information about social, economic, and environmental conditions. Data obtained from interviews, discussions, and observations will be analyzed using a thematic analysis approach. Validity and Reliability To ensure the validity and reliability of qualitative research, several steps that can be taken include: Triangulation: Using various data sources (interviews, observations, and documents) to ensure consistency of information. Member Check: Confirm the findings of the study with the informant to ensure the accuracy of the interpretation. Research Results on Population Density and Irregular Buildings: Building density without good spatial planning makes this area vulnerable to fires, floods, and difficulty accessing emergency infrastructure. Inadequate Basic Infrastructure: Damaged roads, lack of drainage systems, and limited access to clean water result in a low quality of life for the population. Poor Sanitation: Inadequate sanitation facilities such as toilets and lack of waste management systems increase public health risks. Unorganized Waste Management: Indiscriminate waste disposal due to the absence of a good waste management system worsens environmental conditions. Poverty Levels and Low Community Incomes: Most citizens work in the informal sector with low incomes, leaving them without the resources to improve housing conditions.